On single-mode equilibrium and self-organization of reversal field pinch - Gurin, A.A. (Вопросы атомной науки и техники, 2011)
The MGD self-stabilization of kink instability of paramagnetic z-pinch with strong current and some features of the RFP-like quasi-single-mode self-organization as a result of plasma azimuth and z-convection generated by MGD oscillations are studied in single mode approximation on basis of a quasi-linear model.